2022
DOI: 10.1111/1750-3841.16111
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, sterols, and squalene content comparison between two conventional (olive oil and linseed oil) and three non‐conventional vegetable oils (echium oil, hempseed oil, and moringa oil)

Abstract: New sources of bioactive compounds are constantly explored for reformulating healthier foods. This work aimed to explore and characterize the fatty acid profile and sterol content of three non‐conventional oils used in functional food products (hempseed oil, moringa oil, and echium oil) and to compare them with two conventional ones (extra virgin olive oil [EVOO] and linseed oil). Oxidative stability was assessed by determining their acidity value and peroxide content. All oils showed adequate values for acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
1
20
0
1
Order By: Relevance
“…Compared to SD1, SD2, SD3, SD5, and SD6, There was approximately 8–14% SFA of total fatty acids (TFA) in six samples. A previous study found that the SFA content of hempseed oil (10.79%), moringa oil (22.74%), echium oil (10.98%), extra virgin olive oil (16.96%), and linseed oil (8.78%) ( 29 ), which was consistent with the results of this study. A previous study found that the SFA content of some traditional fish and shrimp paste condiments ranged between 46 and 73.14%, indicating that fatty acid composition of SDs was clearly superior to that of traditional fish and shrimp paste condiments ( 30 ).…”
Section: Resultssupporting
confidence: 92%
“…Compared to SD1, SD2, SD3, SD5, and SD6, There was approximately 8–14% SFA of total fatty acids (TFA) in six samples. A previous study found that the SFA content of hempseed oil (10.79%), moringa oil (22.74%), echium oil (10.98%), extra virgin olive oil (16.96%), and linseed oil (8.78%) ( 29 ), which was consistent with the results of this study. A previous study found that the SFA content of some traditional fish and shrimp paste condiments ranged between 46 and 73.14%, indicating that fatty acid composition of SDs was clearly superior to that of traditional fish and shrimp paste condiments ( 30 ).…”
Section: Resultssupporting
confidence: 92%
“…Our study also found ALA (C18:3 n-3) and n-3 PUFAs, such as EPA (20:5 n-3), DPA (22:5 n-3), some n-6 PUFAs such as ETA (C20:3 n-6), EDA (C20:2 n-6) were associated negatively with GADA, some n-6, such as AOA (C18:2 n-6), DTA (C22:4 n-6) were positively associated GADA while the n-3/n-6 ratio and triene/tetraene were negatively associated with GADA, indicating not only in higher proportion of n-3, but also the ratio of n-3/n-6 ratio and triene/tetraene ratio are also important. Moreover, we also found behenic acid (C22:0), NNA (C24:1 n-9), WTA (C24:0), which might come from contamination in vegetable oil ( 58 ), were associated highly with GADA positivity. Taking together with similarly high association of AIA (C18:2 n-6) which also comes from plant oil, it would be supposed that high intake of vegetable oil rich in AIA (C18:2 n-6), either through competing with ALA (C18:3 n-3) or inhibiting the enzymes of SPMs biosynthesis, might increase the development autoimmunity.…”
Section: Discussionmentioning
confidence: 60%
“…The composition of hemp oil resembles sebum and thus supports the regulation of its secretion. 26,27 Patients using 20% Nigella sativa oil lotion showed a reduction in the number of non-inflammatory, inflammatory, and total lesions by approximately 63%, while patients using 5% benzoyl peroxide showed a reduction in the number of these lesions by approximately 47%. Patients using Nigella sativa oil lotion had milder and fewer side effects than those who received lotion with benzoyl peroxide.…”
Section: Discussionmentioning
confidence: 99%